2015
DOI: 10.1007/s40091-015-0089-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect and evaluation of prying action for top- and seat-angle connections

Abstract: Nonlinear finite element (FE) static analyses of top-and seat-angle connections were performed using ABAQUS standard to investigate the influence of connection parameters and its properties on prying action developed due to the interaction between column flange and top angle's vertical leg. Contact phenomenon between two interfaces with finite sliding and bolt pretension in the initial step of analysis was considered in the FE model. FE analysis results were compared with the experimental ones to examine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Due to that observation, the place of formation of the upper plastic hinge in the tension angle's vertical leg has been revised and an additional plastic hinge is supplied in the tension bolts according to the results of FE analyses for the proposed prediction model in determining the ultimate connection moment. FE analysis results [3,4,16] also demonstrated that the distance of the prying force acting point from the centerline of bolthole at the ultimate level of loading mostly depended on the thickness of the tension angle and gage distance from angle heel to the centerline of bolthole. Therefore, it was found that the distance b of the prying force acting point from the centerline of bolthole is a function of the angle thickness of tension angle, t t in combination with gage distance from angle heel to the centerline of bolt hole, g t ' and expressed as [16] …”
Section: Fe Analysis Of Connectionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to that observation, the place of formation of the upper plastic hinge in the tension angle's vertical leg has been revised and an additional plastic hinge is supplied in the tension bolts according to the results of FE analyses for the proposed prediction model in determining the ultimate connection moment. FE analysis results [3,4,16] also demonstrated that the distance of the prying force acting point from the centerline of bolthole at the ultimate level of loading mostly depended on the thickness of the tension angle and gage distance from angle heel to the centerline of bolthole. Therefore, it was found that the distance b of the prying force acting point from the centerline of bolthole is a function of the angle thickness of tension angle, t t in combination with gage distance from angle heel to the centerline of bolt hole, g t ' and expressed as [16] …”
Section: Fe Analysis Of Connectionsmentioning
confidence: 93%
“…Advanced finite element analyses of top-and seat-angle connections were performed by the author and their geometrical and mechanical properties and analysis results were discussed elaborately in the literatures [3,4,15,16]. In those articles with the other's similar investigation [5,6,10], it was observed that plastic yielding of the connections initiated at the toe of the tension angle's fillet and then followed by yielding in the area under the tension bolt head for thinner angles (e.g., for the cases of ⅜" angle thickness), and in the areas of tension bolthole for the cases of thicker angles.…”
Section: Fe Analysis Of Connectionsmentioning
confidence: 99%
“…In their threeparameter power model, Kishi and Chen (1990) considered bending and shear deformations of the angle, but disregarded deformation of bolts for deriving the ultimate moment capacity of angle type of connections. To establish a rational prediction model for representing the M-h r curves of the connections, this effect on connection behaviour needs to be considered (Ahmed and Hasan 2015). Thus, a formulation of determining the ultimate connection moment M u is proposed assuming three types of simple mechanisms of connection failure using the T-stub concept of Eurocode 3 (CEN 1997).…”
Section: List Of Symbols Amentioning
confidence: 99%
“…FE analysis results demonstrated that the distance of the prying force acting point from the centerline of bolthole at the ultimate level of loading mostly depended on the thickness of the top angle and gage distance from angle heel to the centerline of bolthole (Ahmed and Hasan 2015). Therefore, it is shown that the distance b of the prying force acting point from the centerline of bolthole is a function of the angle thickness of top angle, t t , in combination with gage distance from angle heel to the centerline of bolt hole, g 0 t (Fig.…”
Section: Fe Analysis Of Connectionsmentioning
confidence: 99%
See 1 more Smart Citation